Irregular deposits in Norway: Systemic economic crime in the rental market - Johannes Pippidis Lorentzen (Journal of Economic Criminology)
This study investigates the prevalence and patterns of irregular deposit practices and legal breaches concerning tenancy deposits in Norway’s private rental housing sector. Irregularities in handling tenancy deposits can adversely affect tenants, particularly vulnerable groups like students and low-income families. By analysing transaction data from DNB, Norway’s largest bank, covering January 1, 2014, to December 31, 2023, the research reveals that approximately 24.5–42.6 % of rental units experience irregular deposit practices. Many deposits are not stored in legally required accounts, and about 85 % of deposit repayments were round figures, indicating that interest accrued on deposits was often not paid back to tenants. These breaches of the Norwegian Tenancy Act highlight significant concerns within the private renting sector. As the first systematic investigation of irregular deposits in Norway’s rental market, this study provides a foundation for future research and interventions to protect tenant rights and improve compliance with deposit regulations. The findings emphasize the necessity for legislative reforms to strengthen tenant protections and ensure proper deposit-handling practices.The findings emphasize the necessity for legislative reforms to strengthen tenant protections and ensure proper deposit-handling practices.